Pressurized Hot Liquid Extraction with 15% v/v Glycerol-Water as An Effective Environment-Friendly Process to Obtain Durvillaea incurvata and Lessonia spicata Phlorotannin Extracts with Antioxidant and Antihyperglycemic Potential - Fernanda Erpel; María Salomé Mariotti-Celis; Javier Parada; Franco Pedreschi; José Ricardo Pérez-Correa (MDPI AG, 2021)
Brown seaweed phlorotannins have shown the potential to promote several health benefits. Durvillaea incurvata and Lessonia spicata-species that are widely distributed in central and southern Chile-were investigated to obtain phlorotannin extracts with antioxidant and antihyperglycemic potential. The use of an environmentally friendly and food-grade glycerol-based pressurized hot liquid extraction (PHLE) process (15% v/v glycerol water) was assessed for the first time to obtain phlorotannins. Multiple effects were analyzed, including the effect of the species, harvesting area (Las Cruces and Niebla), and anatomical part (holdfast, stipe, and frond) on the extracts' polyphenol content (TPC), antioxidant capacity (AC), and carbohydrate-hydrolyzing enzyme-α-glucosidase and α-amylase-inhibitory activity. Contaminants, such as mannitol, heavy metals (As, Cd, Pb, Hg, and Sn), and 5-hydroxymethylfurfural (HMF), were also determined. The anatomical part used demonstrated a significant impact on the extracts' TPC and AC, with holdfasts showing the highest values (TPC: 95 ± 24 mg phloroglucinol equivalents/g dry extract; DPPH: 400 ± 140 μmol Trolox equivalents/g dry extract; ORAC: 560 ± 130 μmol TE/g dry extract). Accordingly, holdfast extracts presented the most potent α-glucosidase inhibition, with D. incurvata from Niebla showing an activity equivalent to fifteen times that of acarbose. Only one frond and stipe extract showed significant α-glucosidase inhibitory capacity. No α-amylase inhibition was found in any extract. Although no HMF was detected, potentially hazardous cadmium levels (over the French limit) and substantial mannitol concentrations-reaching up to 50% of the extract dry weight-were found in most seaweed samples and extracts. Therefore, further purification steps are suggested if food or pharmaceutical applications are intended for the seaweed PHLE extracts obtained in this study.